The Effect of using Partner Reading Strategy on Student’s English Reading Comprehension Achievement of Hortatory Exposition Text at Madrasah Aliyah Swasta YP. Haji Datuk Abdullah in Academic Year 2021/2022 - Jihan Salsabila; Yusnita Nasution (Medan Resource Center, 2022)
This research aims to find out whether or not there is an influence Significance of the Reading Partner Strategy to improve understanding reading students in class XI at Mas Yp. Haji Datuk Abdullah. Method of This research is a qualitative method. The sample of this research is class XI IPA and XI IPS at Mas Yp. Haji Datuk Abdullah in the 2021/2022 school year. In this research, researcher took 60 students as a sample. The researcher used 10 multiple choice questions to measure students' reading comprehension. In data collection techniques, researchers using pre-test, treatment and post-test by giving tests reading comprehension. The results of this study indicate that there is a significant influence from the use of paired reading strategies. This can be seen from the difference between the students' mean scores from the pre-test and post-test in class experiment which increased from 48 to 74. The mean score of post-test in class control is 31 while the post-test score in the experimental class is 52 more higher than the average value of the control class. That means, pair reading strategy can be applied to improve students' reading comprehension.